Enhancing gender equality in agroforestry systems - Elias, Marlene; Adeyiga, Gloria; Simelton, Elisabeth; Ivanova, Yovita; Paez Valencia, Ana Maria; Vinceti, Barbara; Pagella, Tim (2024)
Agroforestry systems contribute to provisioning food and nutrition, medicine, and income to rural households and play critical cultural roles and regulatory functions around the world. As such, agroforestry is central to the resilience of rural people and landscapes globally. Yet these socio-ecological systems embed and (re)produce significant gender differences and inequalities. This chapter conceptualizes gender in agroforestry, provides illuminating case studies, and outlines a path forward for enhancing gender equality in agroforestry systems